2011
DOI: 10.1007/s00268-011-1179-3
|View full text |Cite
|
Sign up to set email alerts
|

The Necessity and Reliability of Intraoperative Parathyroid Hormone (PTH) Testing in Patients with Mild Hyperparathyroidism and PTH Levels in the Normal Range

Abstract: Intraoperative PTH testing plays an important role in the operative management in 14% of patients with mild hyperparathyroidism. Importantly, a 50% decline in IoPTH level within 15 min of parathyroidectomy is 96.5% reliable in predicting cure in these patients with PTH starting in the normal range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 16 publications
4
44
1
Order By: Relevance
“…There was a 96% cure rate approximately 9 months after surgery with normalized biochemical profiles. Similarly, Alhefdhi et al [25] reported on a series of 142 patients with NHHPT and found that 100% were cured with normal serum calcium after 6 months. Amin et al [38] demonstrated similar cure rates and complication rates for the classic and NHHPT groups.…”
Section: Persistence/recurrence Of Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…There was a 96% cure rate approximately 9 months after surgery with normalized biochemical profiles. Similarly, Alhefdhi et al [25] reported on a series of 142 patients with NHHPT and found that 100% were cured with normal serum calcium after 6 months. Amin et al [38] demonstrated similar cure rates and complication rates for the classic and NHHPT groups.…”
Section: Persistence/recurrence Of Diseasementioning
confidence: 99%
“…50% drop from the highest ioPTH level at 10 minutes after gland excision and a final ioPTH level less than the preincision value [65], .50% drop from the highest ioPTH level at 10 minutes after gland excision and a final ioPTH level within the reference range [66], .50% drop after 5 minutes from highest ioPTH [67], and .50% drop in ioPTH from the preexcision level after 10 minutes [68]. Alhefdhi et al [25] did find that a 50% decline of the preincision value even of patients with NHHPT values is reliable 96.5% of the time, although it takes a longer period of time for this decline to occur in these patients, as well as NCHPT patients [26].…”
Section: Surgicalmentioning
confidence: 99%
See 2 more Smart Citations
“…When PTH levels remain elevated after an excision of the suspected gland, a bilateral neck exploration may be necessary to locate the remaining hypersecreting tissue [56,57]. The IoPTH test is also reliable in mild cases, even if PTH is not elevated [59].…”
Section: Differential Diagnosis and Work-upmentioning
confidence: 99%